2020
DOI: 10.1016/j.psj.2019.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of semen extenders on viability of ISA Brown and Hubbard Flex roosters' sperm stored for 24 h

Abstract: Artificial insemination is used in almost 95% of turkey reproductive flocks and is becoming more important in chickens, particularly broiler breeders, as well as in assisted reproduction of wild birds kept in breeding centers. Diluted semen is recommended for artificial insemination. Pooled semen samples collected twice a week by dorso-abdominal massage from 2 chicken lines: laying—ISA Brown ( ISA-B ) and meat type—Hubbard Flex ( H-F ) were divided into 5 parts: ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
3
9
0
1
Order By: Relevance
“…The effect of semen extenders on morphology and sperm motility in semen stored for 6 h at 4°C described in the presented experiment is consistent with our previous, and other authors' observations in drake (Łukaszewicz, Jerysz, & Chełmońska, 2020), roosters (Dumpala et al, 2006;Łukaszewicz, Jerysz, & Kowalczyk, 2020) and quail semen (Chełmońska et al, 2006). The range of changes depended on the level of lyophilized egg white or yolk in the extender.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The effect of semen extenders on morphology and sperm motility in semen stored for 6 h at 4°C described in the presented experiment is consistent with our previous, and other authors' observations in drake (Łukaszewicz, Jerysz, & Chełmońska, 2020), roosters (Dumpala et al, 2006;Łukaszewicz, Jerysz, & Kowalczyk, 2020) and quail semen (Chełmońska et al, 2006). The range of changes depended on the level of lyophilized egg white or yolk in the extender.…”
Section: Discussionsupporting
confidence: 93%
“…Semen dilution is a very important initial step of in vitro processing, storage and preservation for efficient artificial insemination (Smith et al, 2018). Numerous studies indicate a significant influence of diluents and storage time on sperm morphology and motility parameters in chicken (Donoghue & Wishart, 2000; Dumpala et al, 2006; Hudson et al, 2016; Iaffaldano et al, 2008; Łukaszewicz, Jerysz, & Kowalczyk, 2020; Mphaphathi et al, 2016; Santiago‐Moreno et al, 2012; Siudzińska & Łukaszewicz, 2008; Vasicek et al, 2015), turkey (Di Iorio et al, 2020; Słowińska et al, 2018), guinea fowl (Hudson et al, 2016; Keerthy et al, 2016), ostrich (Smith et al, 2018), capercaillie (Kowalczyk et al, 2012), quail (Chełmońska et al, 2006), duck (Łukaszewicz, Jerysz, & Chełmońska, 2020) and goose (Łukaszewicz, 2002a, 2002b). Semen preservation is also a very important tool necessary in rescue and conservation of bird species and breeds.…”
Section: Introductionmentioning
confidence: 99%
“…The cited authors showed that, similarly to our experiment, bulb-head sperm constituted the highest percentage among the abnormal forms. In addition, in our research on ducks ( Łukaszewicz et al, 2020a , c ), capercaillie ( Kowalczyk et al, 2012 ), pigeons ( Klimowicz et al, 2005 ), and chicken broiler breeders ( Łukaszewicz et al, 2020b ), bulb-head sperm were observed the most frequently. Chełmońska et al (1984) found less live sperm in total (86.2–89.0%) in Kubańska goose semen in relation to both, the northern and southern regional group, but significantly more properly formed sperm (55.7%), especially compared to Rypińska, Kielecka, and Lubelska breeds.…”
Section: Discussionmentioning
confidence: 67%
“…For a practical reason, as well as economic aspects and availability of specific test methods, it is important that the evaluation method is reliable, but also simple, cheap, and possible to be made in a farm condition. Our to date research shows that one of the most reliable methods of semen quality assessment is not the determination of total amount of sperm in the ejaculate, but the number of live properly formed sperm, because only such sperm have the highest potency to fertilize an egg ( Bakst et al, 1994 ; Liu et al, 2008 ; Zawadzka et al, 2015 ; Łukaszewicz et al, 2020a , b , c ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the number of studies that focus on freezing goose semen is very limited. If semen is to be frozen, it needs to be well diluted and of good quality (Ameen et al, 2014;Łukaszewicz et al, 2020). So far, in various studies, researchers have used glycerine (glycerol), DMSO (dimethylsulfoxide), DMA (dimethylacetamide), and DMF (dimethylformamide) as cryoprotectant for cryopreservation of goose semen.…”
Section: Introductionmentioning
confidence: 99%